2005
DOI: 10.1002/jcb.20419
|View full text |Cite
|
Sign up to set email alerts
|

Cadherins and the mammary gland

Abstract: Cadherin cell-cell adhesion proteins are critical for the formation of tissues from single cells. E-and P-cadherin play important roles in the architecture and function of the normal mammary gland. In breast cancers, the expression, or lack thereof, of E-cadherin can differentiate tumor types, whereas the misexpression of either P-cadherin or N-cadherin can be a marker of poor prognosis or increased malignancy, respectively. Additional research is needed to more precisely define the roles of both classical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
73
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 33 publications
0
73
0
4
Order By: Relevance
“…Thus, in ductal carcinoma E-cadherin is expressed, albeit in reduced levels and aberrant cellular locations. Although E-cadherin correlates inversely with the grade of the tumour, reduced E-cadherin expression is not adequate to predict clinical outcome and there are contradictory studies on the association between E-cadherin and survival (Knudsen and Wheelock, 2005). Moreover, it has been reported that in other breast cancers with known poor prognosis, such as inflammatory breast cancer, there is overexpression of E-cadherin (Knudsen and Wheelock, 2005).…”
Section: Dysadherin In Breast Carcinomamentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, in ductal carcinoma E-cadherin is expressed, albeit in reduced levels and aberrant cellular locations. Although E-cadherin correlates inversely with the grade of the tumour, reduced E-cadherin expression is not adequate to predict clinical outcome and there are contradictory studies on the association between E-cadherin and survival (Knudsen and Wheelock, 2005). Moreover, it has been reported that in other breast cancers with known poor prognosis, such as inflammatory breast cancer, there is overexpression of E-cadherin (Knudsen and Wheelock, 2005).…”
Section: Dysadherin In Breast Carcinomamentioning
confidence: 99%
“…Although E-cadherin correlates inversely with the grade of the tumour, reduced E-cadherin expression is not adequate to predict clinical outcome and there are contradictory studies on the association between E-cadherin and survival (Knudsen and Wheelock, 2005). Moreover, it has been reported that in other breast cancers with known poor prognosis, such as inflammatory breast cancer, there is overexpression of E-cadherin (Knudsen and Wheelock, 2005). An interesting concept is that possibly the reduction of E-cadherin expression in breast carcinomas, other than lobular, is transient, due to epigenetic modifications.…”
Section: Dysadherin In Breast Carcinomamentioning
confidence: 99%
See 3 more Smart Citations